Relationships between economic crisis and health education actions in the hospital environment: ecosystem perspective (Research, Society and Development, 2020)
The present study presents the following research question: How are the interrelationships between socioeconomic factors and the educational practice of nurses in the hospital environment given to the caregiver of users with chronic noncommunicable disease? From this question, the objective was to analyze the interrelationships between socioeconomic factors and the educational practice of nurses to caregivers of users with non-communicable chronic disease. Descriptive, exploratory research with qualitative approach, developed in two hospital institutions in a city in the extreme south of Brazil. Data collection took place in October and November 2016, by semi-structured interview. From the data analysis was performed by Thematic Content Analysis, the following categories and subcategories were listed: Sociodemographic profile of participants, Economic and political influences on care and health education actions in the hospital context, Lack of materials and inadequate infrastructure, Overload, Economic and political crisis of the country. The results evidenced the economic and political crisis of the country as elements of interference in the accomplishment of the health education in the hospital context. Thinking about the contemplation of health education actions, performed by nurses in the hospital environment, goes beyond the limited and fragmented view of care and requires a reflection that considers the human being within the complex web of relationships in which it is inserted.